(untitled) (Research, Society and Development, 2020)
Psychodermatological diseases are skin diseases accompanied by mental or emotional disorders. Therefore, it is important to understand this association and find out whether psychotherapy contributes to this dermatological improvement. The present article, then, is an integrative review that aimed to analyze the effectiveness of psychiatric / psychotherapeutic treatment in improving the quality of life of patients with psychodermatological diseases. This is an exploratory study, based on a bibliographic survey on the subject, whose searches were carried out in the databases of the Virtual Health Library (VHL), Medical Literature Analysis and Retrievel System Online (PubMed / Medline) and Cochrane Library, using the terms in the English language: psychiatric treatment, quality of life, skin diseases and anxiety; joined by the Boolean operator AND. The results revealed high levels of stress, anxiety and depression in patients suffering from psoriasis, atopic dermatitis, acne, primary focal hyperhidrosis and chronic eczema. Suicidal behavior was observed in more serious situations. In addition, some psychological disorders contribute to the worsening of existing skin problems. Many patients develop emotional problems secondary to dermatological disease, mainly due to low self-esteem. However, there are few studies on the subject; therefore, it is necessary to find out more about the mind-skin relationship and whether there are psychological disorders causing or influencing diseases and, in this case, enabling an effective treatment.